Cooperative Prototyping Experiments: - Users and Designers Envision a Dental Case Record System - Bødker, Susanne; Grønbæk, Kaj (DAIMI Report Series, 1990)
This paper describes experiments with a design technique that we denote cooperative prototyping. The experiments consider design of a patient case record system for municipal dental clinics in which we used HyperCard$^{TM}$, an off-the-shelf programming enviroment for the Macintosh. In the experiments we tried to achieve a fluent work-like evaluation of prototypes where users envisioned future work with a computer tool, at the same time as we made on-line modifications of prototypes in co-operation with the users when breakdown occur in their work-like evaluation. The experiments showed that it was possible to make a number of direct manipulation changes of prototypes in cooperation with the users, in interplay with their fluent work-like evaluation of these. However, brekdowns occurred in the prototyping process when we reached the limits of the direct manipulation support for modification. From these ecperiences we discuss problems in the process, requirements for design tools, and issues involved in getting going with cooperative prototyping with active user involvement.